AWARENESS ON ANGER MANAGEMENT AMONG ALLIED HEALTH SCIENCE STUDENTS - ASWINI P, HEMALATHA B, SANDHIYA V, SARINA RUBY S, N. PRIYADARSHINI, HAREESH A (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Introduction: Anger is one of the prevalent behavioural problems commonly seen amongst younger and people around them. Anger can lead to aggressiveness in a person. Anger can lead to many problems if it's not controlled properly at the right time such as hurting reputations, destroying relationships, limiting opportunities and can even damage our health. Frustration or feelings excluded from something significant are common causes of anger. Anger is regarded as a protective reaction to any form of vulnerability or fear. However, it can influence a person's choices, sour relationships, and hurt them in other ways. Objective:To assess the level of awareness and understanding of anger management techniques among Allied Health Science Students. Methods:A simplified version of the Personal Anger Assessment Scale will be included in a freshly created questionnaire. Students from Allied Health Science will be part of the study population. The participants of 18 to 20- year-old Allied Health Science students will be involved in the study. After being gathered, the data was statistically examined. Expected outcome:The study aimed to assess the awareness and understanding of anger management among students. Almost 85 percent of the students have knowledge about how to control the anger. Our expected outcome is to reveal that AHS students are aware of how to control their anger. Conclusion:The study concludes that awareness of the anger management among Allied Health Science Students was found to be satisfactory. But there is a need for the stress management session. While students acknowledge the importance of anger management, the results indicate that focused education and training programs are necessary to provide them with useful techniques. Through the development of conflict resolution, stress management, and emotional intelligence, educational institutions can assist students in creating healthy coping strategies. Consequently, this can improve their health, patient care, and professions.